Health‐related quality of life in patients with light chain amyloidosis treated with bortezomib, cyclophosphamide, and dexamethasone ± daratumumab: Results from the ANDROMEDA study. Issue 6 (30th March 2022) - Sanchorawala, Vaishali; Palladini, Giovanni; Minnema, Monique C.; Jaccard, Arnaud; Lee, Hans C.; Gibbs, Simon; Mollee, Peter; Venner, Christopher; Lu, Jin; Schönland, Stefan; Gatt, Moshe; Suzuki, Kenshi; et al.
Abstract: In the phase 3 ANDROMEDA trial, patients treated with daratumumab, bortezomib, cyclophosphamide, and dexamethasone (D‐VCd) had significantly higher rates of organ and hematologic response compared with patients who received VCd alone. Here, we present patient‐reported outcomes (PROs) from the ANDROMEDA trial. PROs were assessed through cycle 6 using three standardized questionnaires. Treatment effect through cycle 6 was measured by a repeated‐measures, mixed‐effects model. The magnitude of changes in PROs versus baseline was generally low, but between‐group differences favored the D‐VCd group. Results were generally consistent irrespective of hematologic, cardiac, or renal responses. More patients in the D‐VCd group experienced meaningful improvements in PROs; median time to improvement was more rapid in the D‐VCd group versus the VCd group. After cycle 6, patients in the D‐VCd group received daratumumab monotherapy and their PRO assessments continued, with improvements in health‐related quality of life (HRQoL) reported through cycle 19. PROs of subgroups with renal and cardiac involvement were consistent with those of the intent‐to‐treat population. These results demonstrate that the previously reported clinical benefits of D‐VCd were achieved without decrement to patients' HRQoL and provide support of D‐VCd in patients with AL amyloidosis.